2019
DOI: 10.3390/geriatrics4040060
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Dysphagia Assessment and Management in Acute Stroke: An Interview Study

Abstract: 1) Background: Patients with dysphagia are at increased risk of stroke-associated pneumonia. There is wide variation in the way patients are screened and assessed. The aim of this study is to explore staff opinions about current practice of dysphagia screening, assessment and clinical management in acute phase stroke. (2) Methods: Fifteen interviews were conducted in five English National Health Service hospitals. Hospitals were selected based on size and performance against national targets for dysphagia scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Hypertension and diabetes are not only the risk factors for stroke, but also the risk factors for dysphagia in stroke patients [ 52 , 53 ]. The results of this study have showed that the incidence of dysphagia in ischemic stroke patients with hypertension and diabetes is significantly higher than that of patients without hypertension and diabetes, which may have a joint effect with chronic diseases affecting the overall function of patients, thereby increasing the risk of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension and diabetes are not only the risk factors for stroke, but also the risk factors for dysphagia in stroke patients [ 52 , 53 ]. The results of this study have showed that the incidence of dysphagia in ischemic stroke patients with hypertension and diabetes is significantly higher than that of patients without hypertension and diabetes, which may have a joint effect with chronic diseases affecting the overall function of patients, thereby increasing the risk of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…This study forms part of a series of studies [11][12][13] that aim to investigate how variation in assessment and management of dysphagia in acute stroke affects development of SAP. The aim of this interview study is to explore the experiences of people with swallowing difficulties following a stroke to give a more rounded picture of delivery of care and ensure that the perspectives of stroke survivors and their informal caregivers are included.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…The aim of this interview study is to explore the experiences of people with swallowing difficulties following a stroke to give a more rounded picture of delivery of care and ensure that the perspectives of stroke survivors and their informal caregivers are included. We wanted to include the patient story of swallowing difficulties post-stroke as a way to better understand the patient experience of dysphagia assessment and management, as well as the views of the staff involved [13,14]. Including the patient story has the potential to highlight variations in practice from the perspective of the persons affected, thereby providing a more inclusive understanding of service delivery.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…Although this review presents a growing consensus on the effectiveness of neurostimulation, physical techniques, and nutritional interventions in enhancing dysphagia recovery, there are still many problems and uncertainties to be explored. In essence, the severity of stroke is influenced by a variety of factors, and due to the complexity of therapeutic interventions, it is difficult to determine exactly what leads to recovery [ 87 ]. The studies reviewed here included both acute and chronic PSD patients, who naturally recover at different rates, making it difficult to determine the effectiveness of clinical interventions.…”
Section: Future Outlookmentioning
confidence: 99%